DEVELOPMENT OF A SALINITY SENSOR USING ETCHED FIBER BRAGG GRATINGS - Zanella, Fellipe Meneghim; Sousa, Kleiton de Morais; Kamikawachi, Ricardo Canute; Beux, Simone (Revista Ciências Exatas, 2023)
This article presents an approach to the application of a salinity sensor based on etched fiber Bragg grating inscribed in single mode fiber. A potential application for this sensor is the salinity monitoring in brine tanks in dairy where this physicochemical parameter is one of the most relevant in quality control in cheese production. Two EFBGs with the same characteristics were used, both sensitive to the variation of the refractive index for the different levels of salinity concentration and temperature measured. Tests were carried out with typical temperatures and concentrations found in brine tanks. A linear regression was used to evaluate the relationship between Baumé degrees and salt concentration, and between the Bragg wavelenght shift and salt concentration, with a non-linear relationship between the parameters being observed.